Genetic diversity and population structure of Eurycoma apiculata in Eastern Sumatra, Indonesia - Zulfahmi Zulfahmi; Parjanto Parjanto; Edi Purwanto; Ahmad Yunus (Society for Indonesian Biodiversity, 2021)
Abstract. Zulfahmi, Parjanto, Purwanto E, Yunus A. 2021. Genetic diversity and population structure of Eurycoma apiculata in Eastern Sumatra, Indonesia. Biodiversitas 22: 4431-4439. Information on genetic variation within and among populations of Eurycoma apiculata plants is important to develop strategies for their conservation, sustainable use, and genetic improvement. To date, no information on genetic variation within and among populations of the E. apiculata has been reported. This study aims to assess genetic diversity within and among populations of E. apiculata based on RAPD markers, and to determine populations to collect E. apiculata genetic material for conservation and breeding programs. Young leaves of E. apiculata were collected from six natural populations. Fifteen RAPD primers were used to assess the genetic diversity of each population. The data obtained were analyzed with POPGEN and Arlequin software. The amplification results of 15 selected primers produced 3-16 loci with all primers 100% polymorphic. At the species level, the mean allele per locus (Na), number of effective alleles (Ne), percentage of polymorphic loci (PPL), Nei’s gene diversity index (He) and Shannon information index (I) were 2.000, 1.244, 100%, 0.167, and 0.286, respectively. At the population level, the mean values for Na, Ne, PPL, He and I were 1.393, 1.312, 39.27%, 0.119, and 0.186, respectively. The highest value of gene diversity within population (He) was found in the Lingga-1 population and the lowest value was found in the Rumbio population. The value of genetic differentiation among populations (GST) of E. apiculata is 0.284, consistent with the results of the AMOVA analysis which found that genetic variation among populations was 23.14%, indicates that the genetic variation of E. apiculata was more stored within populations than among populations. The gene flow (Nm) value of E. apiculata was 1.259 migrants per generation among populations. The Nm value of this species was high category, and could inhibit genetic differentiation among populations. The clustering of E. apiculata population based on the UPGMA dendrogram and PCA was inconsistent with its geographic distribution, reflecting the possibility that genes migration occurred between islands in the past. The main finding of this study was the genetic variation of the E. apiculata mostly stored within the population. Therefore, the population with the highest genetic diversity is a priority for in-situ conservation, and collection of E. apiculata genetic material for ex-situ conservation and breeding programs should be carried out minimum from Lingga-1 and Pokomo populations.